2003
DOI: 10.1002/ab.10049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of competitor density on the aggressiveness of juvenile white seabream (Diplodus sargus cadenati de la Paz, Bauchot and Daget, 1974)

Abstract: The number of aggressive interactions displayed by juveniles of Diplodus sargus cadenati increases progressively in proportion to the number of intruders, with an upper threshold of more than 16 to 18 intruder fish. Beyond this density, resident aggressiveness decreases. The number of aggressive interactions that the resident fish devotes to expelling each intruder shows a clear and significant tendency to decrease as competitor density increases. The resident fish is incapable of rapidly evaluating the outwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
2
7
1
1
Order By: Relevance
“…It is worth noting that the present brain results, in combination with growth, feed efficiency and other biochemical indices concerning the D30 and D35 groups, suggest a change in intra‐population relationships. These results seem to be related to those obtained by Caballero and Castro‐Hdez (2003), who tested the effect of competitor density on the aggressiveness of juvenile white sea bream D. sargus cadenati (de la Paz, Bauchot and Daget) and concluded that the number of aggressive interactions increased progressively as the number of fish increased, with an upper threshold of more than 16–18 fish. Beyond this density and up to 26 fish, aggressiveness decreased.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is worth noting that the present brain results, in combination with growth, feed efficiency and other biochemical indices concerning the D30 and D35 groups, suggest a change in intra‐population relationships. These results seem to be related to those obtained by Caballero and Castro‐Hdez (2003), who tested the effect of competitor density on the aggressiveness of juvenile white sea bream D. sargus cadenati (de la Paz, Bauchot and Daget) and concluded that the number of aggressive interactions increased progressively as the number of fish increased, with an upper threshold of more than 16–18 fish. Beyond this density and up to 26 fish, aggressiveness decreased.…”
Section: Discussionsupporting
confidence: 83%
“…Beyond this density and up to 26 fish, aggressiveness decreased. Although Caballero and Castro‐Hdez (2003) did not test more than 26 fish, their results in relation to those of the present study not only suggest that there is an upper limit in the number of coexisting D. sargus necessary to induce maximum aggressive interactions but also that altered social relationships may be established when an even greater number of fish is present.…”
Section: Discussioncontrasting
confidence: 65%
“…The persistence of the difference in aggressiveness between the hatchery and wild strain may relate to the somewhat lower rearing density of the test fish compared to normal hatchery rearing. This may have permitted a continuance of elevated aggressiveness levels (Caballero & Castro‐Hdez, 2003) in the wild fish. High aggressiveness among the hatchery fish, however, would then also be expected which was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, intensive culture of D. sargus in sea cages has been characterized as unprofitable mainly due to the low growth rate of the species, especially when compared with the widely and successfully reared gilthead sea bream Sparus aurata L. (Divanach, Kentouri, Charalambakis, Pouget & Sterioti 1993; Abellan & Garcia‐Alcazar 1995; Pousão‐Ferreira & Dores 2000). On the other hand, D. sargus is a fish species that develops dominance hierarchy and aggressiveness against its conspecifics (Castro & Santiago 1998; Caballero & Castro 1999; Caballero & Castro‐Hdez 2003), behaviour that cannot be easily manipulated in sea cages, while appropriate rearing conditions, as well as nutritional requirements have not been investigated in depth. Thus, the classification of D. sargus to date as a slow‐growing fish may not represent the species actual potential for fish farming.…”
Section: Introductionmentioning
confidence: 99%